How does money ethics mediate the influence of financial literacy on lifestyle through financial technology? (A Case Study of College Students) - Afni Sirait; Zuhrohtun Zuhrohtun; Novitasari Eviyanti (Journal of International Conference Proceedings, 2025)
Recently, cashless payments have evolved into a credit-based lifestyle. This shift has changed societal habits. This study examines the direct and indirect relationships between financial literacy and lifestyle in FinTech decision-making. It also considers the influence of money ethics as a mediating variable. The study uses a quantitative method. Data was collected by questionnaire and analyzed with SmartPLS. Respondents were accounting students; 90 questionnaires were collected. The results show a direct relationship between financial literacy and FinTech. However, when money ethic is included as a mediating variable, the relationship becomes insignificant. Thus, money ethics do not mediate. Likewise, lifestyle has no direct relationship with financial technology. Money ethics as a mediator also does not provide an indirect relationship with financial technology. Based on data processing results, FinTech use is more influenced by financial understanding and ability than by lifestyle or attitude toward money. This seems likely that the study will develop the discipline of behavioural accounting and mental accounting to be able to further comprehend the aspects that inspire or influence people when they make financial choices.